Chemotaxis of Biofilm Producing Pseudomonas spp. towards Refined Petroleum Oil - Dutta, S.; Singh, P. (Journal of Scientific Research, 2016)
The bioavailability of organic contaminants to the degrading bacteria is a major limitation to efficient bioremediation of sites contaminated with hydrophobic pollutants. Studies were conducted to analyze the presence of biodegrading bacteria on the sites of refinery and garage oil spills with abundance of hydrocarbons. Contaminated soils were collected from these rich hydrocarbon sites and bacteria were isolated from samples using regular bacterial media enriched with petroleum oil. These isolates were characterized for their efficiency to utilize refining petroleum oil as their energy source and then the most common isolate was characterized. Further investigations examine the formation of biofilm by naturally existing oil-degrading bacteria on refine petroleum oil degradation. Here also studied the abilities of these Pseudomonas strains to respond chemo tactically to refine petroleum oil. Microbial chemotaxis plays important role for formation of biofilm. 16S rDNA analysis of the best degrader was found to belong to the Pseudomonas species. Interestingly, one of the best isolates was found to be close to Pseudomonas aeruginosa family.